Multimorbidity in adult patients diagnosed with atopic dermatitis - Szymon Mućka; Martyna Miodonska; Magdalena Mróz Dybowska; Anna Zyźlik; Alicja Grzanka; Robert Pawłowicz; Andrzej Bożek (Dermatology Reports)
Atopic dermatitis (AD) may be associated with other diseases, which could impact the patient's overall health. The aim of this study was to assess the comorbidities observed in patients diagnosed with AD and psoriasis compared to healthy patients. Patients over 18 years old were recruited using the medical databases of dermatology clinics. Initially, 378 patients were selected via an analysis of the ICD-10 codes. Ultimately, 231 patients with atopic dermatitis were included in the study group based on their fulfillment of the Hanifin and Rajka criteria. They included 104 women and 127 men with an age range of 18-62. In patients with AD, selected lifestyle diseases such as obesity and atherosclerosis occurred significantly less frequently than in patients without AD, including those with other dermatoses. In addition, allergic asthma and type 2 diabetes occurred significantly more often in AD patients than in those without AD (p<0.05). In some AD patients, comorbidities are more prevalent, and these are often associated with allergic asthma and type 2 diabetes.